2023
DOI: 10.1111/jgh.16345
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal‐miR‐522‐3p derived from cancer‐associated fibroblasts accelerates tumor metastasis and angiogenesis via repression bone morphogenetic protein 5 in colorectal cancer

Jun Zhang,
Yuliang Pan,
Long Jin
et al.

Abstract: BackgroundColorectal cancer (CRC) is a gastrointestinal tract malignancy. Exosomes secreted by cancer‐associated fibroblasts (CAFs) are reported to participate in tumor progression by delivering noncoding RNA or small proteins. However, the function of exosomal miR‐522‐3p in CRC remains unclear.MethodsCAFs were derived from tumor tissues, and exosomes were identified by western blot or TEM/NTA and originated from CAFs/NFs. The viability, invasion, and migration of HUVECs and CRC cells was examined using MTT, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…The examination’s primary focus is the CTC count, with a positive threshold of ≥ 5, typically representing a poor prognosis. The persistence of CTC following therapy is associated with a poorer prognosis, and studies have demonstrated that changes in the quantity of CTC provide better predictive information than baseline CTC status ( 76 , 77 ). The number of CTCs present before beginning neoadjuvant therapy hurts survival, according to a meta-analysis of 2239 breast cancer patients from 21 trials (246) ( 60 ).…”
Section: Importtant Areas Of Clinical Applications Of Ctcs、ctdna and Evsmentioning
confidence: 99%
“…The examination’s primary focus is the CTC count, with a positive threshold of ≥ 5, typically representing a poor prognosis. The persistence of CTC following therapy is associated with a poorer prognosis, and studies have demonstrated that changes in the quantity of CTC provide better predictive information than baseline CTC status ( 76 , 77 ). The number of CTCs present before beginning neoadjuvant therapy hurts survival, according to a meta-analysis of 2239 breast cancer patients from 21 trials (246) ( 60 ).…”
Section: Importtant Areas Of Clinical Applications Of Ctcs、ctdna and Evsmentioning
confidence: 99%